Cost and Management Accounting Practices, ICT Usage and Performance of Secondary Schools in Uganda: A Case of South Western Uganda - Abanis, Turyahebwa; Natwijuka, Crispus; Sunday, Arthur; Byamukama, Eliab Mpora (Research Journal of Finance and Accounting, 2023)
This article accounts for the findings from a study conducted in secondary schools located in south western Uganda. The study was about Cost and Management Accounting Practices, ICT Usage and Financial Performance of Secondary Schools. This study adopted a cross-sectional and correlational design. Questionnaires were administered to 435 secondary schools. The Unit of analysis was secondary schools and the unit of inquiry was head teachers/their representatives.The findings indicate that the adjusted R² is 27.4% and the F-ratio (F = 9.122) is significant. This means that the total predictive power of cost and management accounting and ICT adoption account for 27.4% in financial performance of secondary schools. (R² = 0.274, p <0.01). The results supported the earlier set three (3) hypotheses in the literature review. The results emphasize that cost and management accounting practices highly influence financial performance of secondary schools.The study emphasized that Education is acute to the generation of strong, and enlightened countries, to which Uganda aspires to be. In recent years, Uganda Primary Education (UPE) has procreated large proliferations in the number of students yearning secondary education in Uganda. Private secondary schools have been established to encounter the superfluous demand. Without steadfast cost and management systems to guarantee stable financial performance, the secondary schools must, as any other enterprise throughout the world, become financially autonomous, their survival is in doubt.